Membentuk Nilai Kultur dan Karakter Bangsa bagi Anak Usia Dini - Hayeemaming, Marwan; shofwan, arif muzayin; hidayah, choirul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
The formation of cultural values ​​and national character must start from an early age. Because, early childhood is a sensitive period that has very rapid physical, motor, intellectual, and social development. This descriptive qualitative research using a literature study examines how to shape cultural values ​​and national character in early childhood. The data analysis technique uses content analysis by sorting out data according to the problem and research objectives. This paper produces several things as follows. First, some cultural values ​​and national character that must be formed in early childhood according to the Ministry of National Education, including religious, honest, tolerance, discipline, hard work, creativity, independence, democratic, curiosity, national spirit, love for the homeland, appreciate achievement, friendly, love peace, love to read, care for the environment, care about social, and responsibility. Second, several other character elements that must be built in early childhood, including initiative, ethics, critical thinking, willingness to learn, commitment, motivation, enthusiasm, reliability, verbal communication, creativity, analytical ability, can cope with stress, management of self, able to solve problems, can summarize, cooperative, flexible, teamwork, independent, able to listen, tough, logical argumentation, and time management